The place and role of papal nuncios in the peace missions of the church as reflected by new types of safety challenges (Academic Journal of Internal Affairs, 2021)
The Catholic Church has exclusive opportunities in international crisis management and peacekeeping. The Catholic Church is – beside being a religious congregation – an international legal entity of the Apostolic See. The present pope tries to position the whole dicastery system as a peacemaker. Due to the nature of the situation papal nuncios and diplomatic missions of the Apostolic See play outstanding roles in these missions. The diplomats in conflict areas and in international organisations play especially important roles. The Church Law Code presents only briefly and first of all from legal point of view the place of nuncios in the Canon. In addition to that CIC follows the classical distribution system: it writes about tasks of nuncios in connection with partial churches and countries. But a peace mission interlaces the whole mission of a nuncio, it is much more complicated than a simple legal approach and simultaneously an exciting and versatile activity. This diversity is presented in this paper.
Keywords: church diplomacy; Apostolic See; papal nuncios; peace mission